THE CONSTITUTIONALITY OF THE DEJUDICIALIZATION OF MORTGAGES: AN ANALYSIS OF THE DIRECT ACTION OF UNCONSTITUTIONALITY 7601 AND ITS EFFECTS ON CREDIT RELATIONS - Silva Arantes, Wagner; Maria Da Silva Mhirdaui, Rogéria; Roberto Costa, Marcos (Revista Gênero e Interdisciplinaridade, 2025)
Law 14,711/2023, which provides for the dejudicialization of mortgages, was designed with the purpose of simplifying and speeding up the procedure for enforcing credits backed by mortgages and fiduciary alienation. With the new law, the foreclosure of the mortgage will be carried out without the interference of the judiciary represented by the extrajudicial procedure which, in theory, has greater efficiency to the process. The present work, which is presented with an exploratory and descriptive purpose, aims to discuss the impacts caused by the reform in the Brazilian legal system, in the theme of the protection of fundamental rights. To this end, a qualitative approach will be used, through a method of bibliographic and documentary review, focusing on the analysis of jurisprudence, Brazilian legislation and academic articles. Thus, it will be possible to critically examine the measure and reflect on the advances and setbacks caused by the reform. If, on the one hand, we note that dejudicialization can be understood as an advance, especially as it makes commercial relations and the financial market more efficient and facilitates access to credit, on the other hand, there is a significant concern regarding the relativization of fundamental rights, property and due process. Extrajudicial execution, by dispensing with due process, puts at risk the balance between the interests of creditors and the protection of debtors. Thus, dejudicialization is innovative, however, it goes backwards with regard to the protection of fundamental rights, especially when it comes to the fundamental protection of property and due process of law.